Methodological aspects of using the game in teaching vocabulary - Nurkenova S.S. Нуркенова С.С.; Kemelbekova E.A. Кемельбекова Э.А.; Mukanova S.K. Муканова С.К.; Kereikhanova Z.S. Керейханова З.С. (Рroblems of engineering and professional education, 2023)
t is known that the game is very important in teaching a foreign language. Many teachers pay attention to the effect of this method in teaching a foreign language. In the course of the game, all the possibilities of the students are revealed.